Financial performance of Islamic banks in Malaysia: a comparative study of Bank Islam Malaysia Berhad and Kuwait Finance House / Nor Khairunnisa Simon - Simon, Nor Khairunnisa (Faculty of Business and Management, 2010)
This report has been done to study the financial performance of Bank Islam Malaysia Berhad and Kuwait Finance House. For completion of this report, secondary data and other method such as procedure for analysis of data which derived from the annual report of each banks and data processing method which is ratio analysis technique has been used as a data collection. The data are taken from external sources such as Bank Negara Annual Report, BIMB annual reports, KFH annual reports, various publication, books, newspaper articles and magazines. The study examines 4 type of ratios include (1) Return on Assets, (2) Return on Equity, (3) Financing deposit ratio, (4) Non performing financial. The result of the fianacial ratios shows that the Kuwait Finance House is good in the performance in previous three years compared to Bank Islam Malaysia. This study also will give the management, researcher and financial analyst or lender information regarding to performance of both banks that can be used for the future prospect.